Anti-apoptotic protein Bcl-2 contributes to the determination of reserve cells during myogenic differentiation of C2C12 cells - Nagata, Yosuke; Tomimori, Jun; Hagiwara, Tomoharu (In vitro cellular & developmental biology. Animal, 2024)
Summary Skeletal muscle's regenerative ability is vital for maintaining muscle function, but chronic diseases like Duchenne muscular dystrophy can deplete this capacity. Muscle satellite cells, quiescent in normal situations, are activated during muscle injury, expressing myogenic regulatory factors, and producing myogenic progenitor cells. It was reported that muscle stem cells in primary culture and reserve cells in C2C12 cells express anti-apoptotic protein Bcl-2. Although the role of Bcl-2 expressed in myogenic cells has been thought to be to enhance cell viability, we hypothesized that Bcl-2 may promote the formation of reserve cells. The expression pattern analysis showed the expression of Bcl-2 in undifferentiated mononucleated cells, emphasizing its usefulness as a reserve cell marker and reminding us that cells expressing Bcl-2 have low proliferative potential. Silencing of Bcl-2 by transfection with siRNA decreased cell viability and the number of reserve cells, while overexpression of Bcl-2 not only increases cell viability but also inhibits muscle differentiation and proliferation. These results emphasize dual roles of Bcl-2 in protecting cells from apoptosis and contributing to reserve cell formation by regulating myoblast proliferation and/or differentiation. Overall, the study sheds light on the multifaceted role of Bcl-2 in the maintenance of skeletal muscle regeneration.